Windfall : new and selected poems - Anderson, Maggie (Pitt poetry series., 2000)
Windfall includes poems from three previous books by Maggie Anderson, along with a generous selection of new work. In this collection we can see over two decades of the growth of a poet memorable for the clarity, strength, and urgency of her voice. Anderson's poems entangle a language, a history, and a group of belongings, and she is both at home and a foreigner in the places she invokes. Every place in these poems seems inhabitable, yet the tensions of these deceptively quiet lines develop out of the clear reluctance or inability of the poet to sit still. Maggie Anderson writes out of deep g.